Abiotic Stress: Molecular Genetics and Genomics - Mukesh Jain (Frontiers Research Topics, 2014)
Abiotic stresses are the major cause that limits productivity of crop plants worldwide. Plants have developed intricate machinery to respond and adapt over these adverse environmental conditions both at physiological and molecular levels. Due to increasing problems of abiotic stresses, plant biotechnologists and breeders need to employ new approaches to improve abiotic stress tolerance in crop plants. Although current research has divulged several key genes, gene regulatory networks and quantitative trait loci that mediate plant responses to various abiotic stresses, the comprehensive understanding of this complex trait is still not available. This e-book is focused on molecular genetics and genomics approaches to understand the plant response/adaptation to various abiotic stresses. It includes different types of articles (original research, method, opinion and review) that provide current insights into different aspects of plant responses and adaptation to abiotic stresses.